2014
DOI: 10.1007/s11047-014-9426-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA walker circuits: computational potential, design, and verification

Abstract: Abstract. Unlike their traditional, silicon counterparts, DNA computers have natural interfaces with both chemical and biological systems. These can be used for a number of applications, including the precise arrangement of matter at the nanoscale and the creation of smart biosensors. Like silicon circuits, DNA strand displacement systems (DSD) can evaluate non-trivial functions. However, these systems can be slow and are susceptible to errors. It has been suggested that localised hybridization reactions could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…[48] experimentally demonstrated that a walker can be directed to any leaf in a complete two-level binary tree by selectively unblocking the anchorages. In [16,15], we have studied the expressive power of DNA walker circuits implemented by this technology and showed that the circuits can compute any Boolean function through reduction to 3-CNF. Compared to DNA strand displacement systems in solution, an advantage of this technology is its spatial locality, but we have found that the undirected nature of the tracks imposes limitations on the use of parallelism.…”
Section: Background On Molecular Walkersmentioning
confidence: 99%
See 2 more Smart Citations
“…[48] experimentally demonstrated that a walker can be directed to any leaf in a complete two-level binary tree by selectively unblocking the anchorages. In [16,15], we have studied the expressive power of DNA walker circuits implemented by this technology and showed that the circuits can compute any Boolean function through reduction to 3-CNF. Compared to DNA strand displacement systems in solution, an advantage of this technology is its spatial locality, but we have found that the undirected nature of the tracks imposes limitations on the use of parallelism.…”
Section: Background On Molecular Walkersmentioning
confidence: 99%
“…The behaviour of molecular walkers is inherently probabilistic and we have studied their performance and reliability in [15,14,16]. In [38], we have developed techniques to automatically synthesise rates so that a given quantitative requirement is guaranteed to be satisfied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRISM has been used previously to model a variety of biological case studies, including DNA circuits and DNA nanorobotic walkers [11,27]. PRISM also is used widely to model probabilistic protocols, e.g., in distributed sensor networks, and stochastic multi-player games [26].…”
Section: Related Workmentioning
confidence: 99%
“…Depending on prior input, certain anchorages can be blocked, which in turn directs the walker at each junction. A Markov chain model of the walker was developed [5] previously, and in this paper we apply model checking with FAU, using the parameter set ε = 10 −6 and δ = 10 −8 . We analyse three XOR-circuits, from Fig.…”
Section: Dna Strand Displacementmentioning
confidence: 99%